A Postponement Model for Demand Management - Iyer, Ananth (Institutional Knowledge at Singapore Management University, 2003)
In this paper, demand postponement is analyzed as a strategy to handle potential demand surges. Under demand postponement, a fraction of the demands from the regular period are postponed and satisfied during a postponement period. This permits capacity to be procured to satisfy the postponed demands. A reimbursement per unit is paid to customers whose demands are postponed. The basic idea is that by preempting stockouts through demand postponement, overall stockout costs can be reduced. A two-stage capacity planning problem under demand postponement is formulated and solved. A power range class of distributions is proposed to capture the nature of demand surges. It is shown that: 1. the value of postponement may be significant depending on cost and demand parameters, 2. a postponement strategy may lead to reduced investment initial capacity, and 3. it may be optimal to do not demand postponement over a range of demands even after observing a higher demand signal.